Public Health Agency of Sweden's Brief Report: Pregnant and postpartum women with severe acute respiratory syndrome coronavirus 2 infection in intensive care in Sweden. (13th June 2020) - Collin, Julius; Byström, Emma; Carnahan, AnnaSara; Ahrne, Malin
Abstract: The Public Health Agency of Sweden has analyzed how many pregnant and postpartum women with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection have been treated in intensive care units (ICU) in Sweden between 19 March and 20 April 2020 compared with non‐pregnant women of similar age. Cases were identified in a special reporting module within the Swedish Intensive Care Registry (SIR). Fifty‐three women aged 20‐45 years with SARS‐CoV‐2 were reported in SIR, and 13 of these women were either pregnant or postpartum (<1 week). The results indicate that the risk of being admitted to ICU may be higher in pregnant and postpartum women with laboratory‐confirmed SARS‐CoV‐2 in Sweden, compared with non‐pregnant women of similar age.